THE PORTRAYAL OF PERSONA AND SHADOW IN NORMAL PEOPLE BY SALLY ROONEY: AN ARCHETYPES STUDY - Putri Rahayu; Suprayogi Suprayogi (English Literature Study Program, Faculty of Arts and Education Universitas Teknokrat Indo, 2023)
This study aims to reveal the archetypes of Persona and Shadow in the characters in the novel Normal People by Sally Rooney. Meanwhile, the characters that were used as research objects consisted of three characters Connell, Marianne, and Alan. Of the three characters, the persona and shadow within them are the main objects in this study. Meanwhile, this research will use a descriptive qualitative method. The data source for this research was taken from the novel Normal People by Sally Rooney, while the research data consisted of dialogue and narration in the novel. This study uses the psychology of literature with a focus on Jung's archetypes, especially Persona and Shadow. The finding revealed that persona appears in all three characters, namely Connell, Marianne, and Alan. This persona is shown by self-confidence, intelligence, and power which is a good mask for the situation and environment in which they live. Meanwhile, a shadow appears in the lives of the three characters with different tendencies, ranging from acts of violence, bullying, and cowardice within. Therefore, this study concluded that persona and shadow appear in the three characters in different forms of action, behavior, and feeling. Keywords: jung analysis, normal people, persona, pyschology of literature, shadow.